Sound quality recognition using optimal wavelet-packet transform and artificial neural network methods. (January 2016) - Xing, Y.F.; Wang, Y.S.; Shi, L.; Guo, H.; Chen, H.
Abstract: According to the human perceptional characteristics, a method combined by the optimal wavelet-packet transform and artificial neural network, so-called OWPT–ANN model, for psychoacoustical recognition is presented. Comparisons of time–frequency analysis methods are performed, and an OWPT with 21 critical bands is designed for feature extraction of a sound, as is a three-layer back-propagation ANN for sound quality (SQ) recognition. Focusing on the loudness and sharpness, the OWPT–ANN model is applied on vehicle noises under different working conditions. Experimental verifications show that the OWPT can effectively transfer a sound into a time-varying energy pattern as that in the human auditory system. The errors of loudness and sharpness of vehicle noise from the OWPT–ANN are all less than 5%, which suggest a good accuracy of the OWPT–ANN model in SQ recognition. The proposed methodology might be regarded as a promising technique for signal processing in the human-hearing related fields in engineering. Highlights: An intelligent method combined by the WPT and ANN for sound quality is proposed The WPT can be used for simulating the critical bands in human hearing system. An OWPT–ANN is established and verified for SQ recognition of vehicle noises. The OWPT–ANN model is a promising technique in SQ evaluation engineering.